STUDI FENOMENOLOGI: EKSPLORASI KEBUTUHAN PSIKOSOSIAL PASIEN CA. MAMMAE DI RSUD PROF. DR. W.Z JOHANNES KUPANG - Sr. Maria Laly (CHMK NURSING SCIENTIFIC JOURNAL, 2018)
ABSTRACT Self-esteem is an individual’s assessment, feelings and opinion, both positive and negative towards his/herself. Self-esteem is often disrupted by adolescent due to a changing self-concept. The factors that can influence adolescent self-esteem include age, gender, education, traumatic experiences and self-ideals. The purpose of this research was to determine the factors that influence adolescent self-esteem (ages 12-22 years). The method of research is descriptive; and data were collected by using questionnaires. The samples in this study were 66 respondents. Chosen of through total sampling. Based on the results of the Chi-Square test there was influence of the factors of age, sex, education, traumatic experiences and self-ideals to ward self-esteem with p-value<0,05. Most respondents (51.5%) had low self-esteem. The results of logistic regression analysis showed that the most dominant factors affecting self-esteem was self-ideals with p-value= 0.012 <0.25, with OR = 8.473 and C, I = 1.604-44.746. From the results of this study, it is expected that prison officials give more attention to psychological problems of inmates, recognize and carry out processing by offering mentoring, phycology assessment and spiritual guidance for youth by a psychiatrist priests based on inmates religion while in prison in order to improve and maintain high self-esteem. Keywords: Self-esteem, age, gender, educational, traumatic experiences, self-ideal